Comparison of optical absorption and thermoluminescence in LiF:Mg, TI (TLD-100) following irradiation by high energy protons and 90Sr/90Y beta rays. (March 2020) - Reshes, G.; Eliyahu, I.; Oster, L.; Horowitz, Y.S.; Biderman, S.; Ginsburg, D.; Olko, P.; Bilski, P.; Swakon, J.; Horwacik, T.
Abstract: The optical absorption (OA) energy spectrum and thermoluminescence (TL) glow curve characteristics of LiF:Mg, Ti (TLD-100) samples following 90Sr/90Y beta ray irradiation and high energy proton irradiation are compared for the first time. The beta ray irradiations were carried at room temperature at a dose rate in LiF of approximately 0.13 Gy min −1 . Proton irradiations were carried out at energies of 20 MeV, 40 MeV and 58 MeV with initial stopping powers of 5.5, 3.2 and 2.3 keV μm −1 respectively. Proton escaping the TL detectors had average energies 55.9, 37.1, 14.4 MeV and the corresponding stopping power in LiF 2.43, 3.36, 7.19 keV μm −1 respectively. All proton irradiations were carried out at a dose of 1124 Gy in LiF and the beta irradiations at a dose of 970 Gy in LIF. The OA spectra were deconvoluted with Gaussian Peak Shapes using a commercial "Peak-Fit" non-linear curve fitting program from Jandel Scientific. The Gaussian bands are characterized by the two parameters of band energy and width. The glow curves were deconvoluted using the Ben Gurion University mixed-order kinetics program. In the analysis first-order kinetics glow peak shapes were employed. The major difference between the two spectra is in the optical density of the F band at 5.08 eV; 0.17 compared to an average value of 0.33 following beta and proton irradiation respectively. The relative intensity, protons to betas, of the other OA bands are remarkably similar within the experimental errors and indicate that the traps associated with these OA bands are not created by the irradiation. It is demonstrated that proton irradiation of LiF:Mg, Ti (TLD-100) creates F centers with 75% greater efficiency than 90 Sr/ 90 Y beta particles. This finding lends further support to the conclusion that track structure theory is unable to accurately predict proton relative efficiencies in LiF:Mg, Ti The results are also interpreted in the framework the spatially correlated trapping center/luminescent center model for composite peak 5 in LiF:Mg, Ti. Highlights: Optical absorption. Thermoluminescence in LiF:Mg, TI (TLD-100). High energy protons.